2008
DOI: 10.1016/s0035-9203(08)70023-3
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 does not play a role in the control of in vitro Burkholderia pseudomallei growth

Abstract: Burkholderia pseudomallei, the causative agent of melioidosis, is an important intracellular pathogen in tropical regions. TANK-binding kinase (TBK1), part of the pathway that induces transcription of Type I interferon genes, has been demonstrated to play an important role in controlling intracellular bacterial infections. To investigate the role of tbk1 in protecting against B. pseudomallei we developed tbk1-deficient cell lines by using shRNA for transient knockdown of the tbk1 gene in HeLa and RAW 264.7 cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Our results are consistent with those reported previously by another group of investigators, who demonstrated that TBK1 knockdown macrophages do not interfere with intracellular survival of this bacterium (20). Moreover, inactivation of TRIF, another adaptor molecule in the MyD88‐independent pathway, does not affect survival of infected animals, suggesting that only the MyD88‐dependent pathway is needed to control wild type infection (21).…”
Section: Discussionsupporting
confidence: 94%
“…Our results are consistent with those reported previously by another group of investigators, who demonstrated that TBK1 knockdown macrophages do not interfere with intracellular survival of this bacterium (20). Moreover, inactivation of TRIF, another adaptor molecule in the MyD88‐independent pathway, does not affect survival of infected animals, suggesting that only the MyD88‐dependent pathway is needed to control wild type infection (21).…”
Section: Discussionsupporting
confidence: 94%
“…The data showed the same bacterial counts in TBK1 deficient cells and control cells. Thus the Myd88-independent pathway is not able to control B. pseudomallei infection, but is able to control Escherichia coli and Brucella melitensis [7]. Type II interferon (IFN-γ) is produced within the first 24 hours of interaction between the host and B. pseudomallei and has an important role to play against B. pseudomallei.…”
mentioning
confidence: 99%